Effect of reduced doses of a post-emergence graminicide mixture to control Lolium rigidum G. in winter wheat under direct drilling in Mediterranean environment - Barros, José (2005)
A study was carried out over 2 years (2002/2003 and 2003/2004) on a private farm in the Alentejo (Évora), in the South of Portugal where rainfed wheat is sown after the beginning of the winter rainfall season. A no-till wheat crop was used as this technology provides the necessary soil bearing capacity for the post-emergence application at different weed development stages. A mixture of diclofop-methyl+fenoxaprop-p-ethyl+mefenepir-diethyl was used at three doses on two timings with three different application volumes. The results indicate that lower herbicide concentrations using higher water application volumes decreased weed control efficiency at both weed development stages. For every treatment, the first weed development stage (beginning of tillering) provided a higher crop grain yield. At this stage, both weeds and crop are more sensitive to the herbicide and as consequence the higher weed control efficiency was not reflected in a higher grain yield, due to some crop fitotoxicity caused by the herbicide when its concentration increased. Weed reinfestation was low for both application timings, indicating that lower herbicide doses than the recommended ones (2.5–31 ha−1) or those normally used by the Portuguese farmers (21 ha−1) can be used for a satisfactory control of Lolium rigidum G. In winter wheat post-emergence treatments can reduce doses if combined with adequate application volumes and early application timings. When herbicide application was delayed (complete tillering) higher herbicide doses were necessary to achieve the highest crop yield.